Significance of the Entire Appendiceal Evaluation in the Diagnosis of Serrated Lesions, Low-Grade Appendiceal Mucinous Neoplasm, and Appendiceal Diverticulosis Disease - Li, Fang; Lu, Yiyan; Hou, Fang; Ma, Ruiqing; Wang, Dezhong; Qi, Changhai (Frontiers in Oncology, 2022)
ABSTRACT Objective: To investigate the significance of the entire appendiceal evaluation in the pathological diagnosis of appendiceal serrated lesions, low-grade appendiceal mucinous neoplasm (LAMN) and appendiceal diverticulosis disease (ADD). Methods: A total of 702 appendectomy specimens diagnosed from 2017 to 2020 were reviewed retrospectively. The specimens were divided into two groups according to the different sampling procedures. In group 1, the vast majority of 337 specimens were partially submitted by the routine sampling within 18 months from October 2017 to March 2019. In group 2, 365 of specimens were entirely submitted and examined within 18 months from April 2019 to October 2020. The incidence and pathological features of serrated lesions, LAMN and ADD in the two groups were compared and analyzed. The clinicopathological characteristics between different entities were also studied. Results: 40 appendiceal serrated lesions, 8 LAMNs and 21 diverticula were accidentally detected in 702 appendectomy specimens. As compared with group 1, the incidence of appendiceal serrated lesions in group 2 was significantly increased (9.3 vs. 1.8%, P < 0.01), especially for the serrated lesions without dysplasia (7.4 vs. 1.2%, P < 0.01). The entirely sampling revealed that loss of lamina propria and replacement with dysplastic mucinous epithelium were statistically significantly associated with LAMN rather than serrated lesions and ADD (P < 0.01 and P < 0.01, respectively). Mural mucin deposition and fibrosis were useful features to distinguish LAMN from simple serrated lesions (P < 0.01 and P < 0.05, respectively), but mucin deposition was useless for the distinction between LAMN and ADD (P > 0.05) or serrated lesions combined with ADD. Conclusion: Our study highlights the importance and necessity of careful gross assessment with histologic examination of the entire appendectomy specimen, since the association with unexpected appendiceal lesions is significant and cannot be ignored. The entirely submitted appendix is more sensitive for detection of appendiceal serrated lesions. In addition, thorough examination and evaluation are essential to distinguish the key pathological features between appendiceal serrated lesions, LAMN and ADD.